United States response to the COVID-19 pandemic, January–November 2020. Issue 1 (5th January 2022) - Alexander, Mathew; Unruh, Lynn; Koval, Andriy; Belanger, William
Abstract: As of November 2020, the United States leads the world in confirmed coronavirus disease 2019 (COVID-19) cases and deaths. Over the past 10 months, the United States has experienced three peaks in new cases, with the most recent spike in November setting new records. Inaction and the lack of a scientifically informed, unified response have contributed to the sustained spread of COVID-19 in the United States. This paper describes major events and findings from the domestic response to COVID-19 from January to November 2020, including on preventing transmission, COVID-19 testing and contact tracing, ensuring sufficient physical infrastructure and healthcare workforce, paying for services, and governance. We further reflect on the public health response to-date and analyse the link between key policy decisions (e.g. closing, reopening) and COVID-19 cases in three states that are representative of the broader regions that have experienced spikes in cases. Finally, as we approach the winter months and undergo a change in national leadership, we highlight some considerations for the ongoing COVID-19 response and the broader United States healthcare system. These findings describe why the United States has failed to contain COVID-19 effectively to-date and can serve as a reference in the continued response to COVID-19 and future pandemics.